If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1v + -2(1 + -6v) = -24 -1v + (1 * -2 + -6v * -2) = -24 -1v + (-2 + 12v) = -24 Reorder the terms: -2 + -1v + 12v = -24 Combine like terms: -1v + 12v = 11v -2 + 11v = -24 Solving -2 + 11v = -24 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 11v = -24 + 2 Combine like terms: -2 + 2 = 0 0 + 11v = -24 + 2 11v = -24 + 2 Combine like terms: -24 + 2 = -22 11v = -22 Divide each side by '11'. v = -2 Simplifying v = -2
| 188=-24[x+5] | | 4(x-10)=32 | | -6z-24+10z=16 | | 33-x=22 | | 14x+-4+12x=1+x | | 3x+7+14=42 | | 12-48x=0 | | 8B+16-3A=-5A+8B+120 | | (3x)(2x+4)=5x^2-35 | | 4f-12=-5f+51 | | 0.5[6x-6]=0.25[x+54] | | -2(x+4)=6x+16 | | 3cosx=cosx+1 | | 3t+2+4t-6t=4+1 | | 2t^3-3t^2+11=0 | | 7x-(4x-7)= | | 10x(-4)= | | 7a+(-4)+2a=3a+(-2) | | -10.1x+1.5=50.7-1.4x | | 3(p+5)= | | 4-9b=176 | | f(x)=2+2x | | 25=x+2 | | 96=-5n-2(-3+5n) | | 5(2-2n)=-15 | | 2y-0=6 | | 8x+1-7x=0 | | 10(a+6.2)=102 | | 4C-10=6 | | 3a+(-4)=-2 | | 8-x=1 | | 5x-2(x-3)=-6+5x+8 |